(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2017)
The natural vegetation of the Kuyalnytskyi estuary valley characterized by the high level of phyto- and coenodiversity and satisfactory condition. Its current territorial differentiation are depends from geomorphological conditions and anthropogenic factors influence. Large areas were drained and covered by halophylic vegetation after catastrophic reduction of the estuary. The pioneer Therosalicornietea halophytic vegetation are occupied lowest periodically flooded areas The saline grassland strips and saline steppe vegetation of Festuco-Puccinellietea were formed in drier conditions around the estuary. The dense stands of Phragmites australis with Tripolium pannonicum were in wedging fresh water places. The dry slops are occupied by steppe Festuco-Brometea communities and shrub Rhamno-Prunetea communities, and also by artificial trees and shrubbery Salicetea purpureae plantings. The steppe vegetation were dominated on the left slops, shrub and tree-shrub vegetation were prevailed on the right slops. Tanaceto millefolii-Galatellion villosae communities of the saline steppe were distributed in the southern part of the valley only and occupied large areas on the right estuary bank. Phragmito-Juncetum maritimi (class Juncetea maritimi), Anisantho tectori-Glycyrrhizetum glabrae (Festuco-Puccinellietea), Schoenoplectetum litoralis (Phragmito-Magnocaricetea), Stipa pulcherrima comm. and Stipa tirsa comm. (Festuco-Brometea) were rarest communities in the valley estuary.